"There's Not Enough Bodies to Do the Demand:" An Exploration of Key Stakeholder Views on the Role of Health Service Capacity in Shaping Cancer Outcomes in 7 International Cancer Benchmarking Partnership Countries - Maureen Seguin; Melanie Morris; Martin McKee; Ellen Nolte (Kerman University of Medical Sciences, 2022)
BackgroundDifferences in cancer survival are shaped by differences in health system capacity in workforce and infrastructure. Part of the International Cancer Benchmarking Partnership (ICBP), this study explored stakeholders' perceptions of the role of health system capacity necessary for cancer care in influencing cancer survival in 7 high-income countries. MethodsWe conducted semi-structured interviews with 79 key informants from national, regional, and local tiers of health systems, professional bodies, patient associations, and academic experts in Australia, Canada, Denmark, Ireland, New Zealand, Norway, and the United Kingdom. Data collection was guided by a conceptual model linking characteristics of health systems and cancer survival along the cancer patient journey, from recognition of symptoms at pre-diagnostic stages through to survivorship or death. Data were analysed using a thematic approach. ResultsWe identified 3 themes as important in shaping cancer outcomes: primary care and access to diagnostic evaluation, specialist care and access to treatment, and workforce pertaining to diagnostic and treatment phases. Improved infrastructure for diagnosis and treatment had improved cancer outcomes in all jurisdictions. However, this was seen as insufficient if staffing was inadequate. Consolidation of services and greater surgical specialisation was important in some jurisdictions if accompanied by a reconfiguration of services, in particular the creation of specialist multidisciplinary teams, along with supporting capacity in the wider health system. Staff shortages were commonly cited as reasons why some jurisdictions lagged behind others. ConclusionContinued improvement in cancer outcomes will require sustained investment in plans to deliver and maintain the workforce engaged in cancer care and in the infrastructure on which they depend. However, strategic plans must recognise that systems for cancer care do not work in isolation from the rest of the health system and a whole systems approach is essential if we are to improve outcomes for an ageing, increasingly multimorbid population.